Typological Study of Financialized Housing in Chile: Verticalization in Estación Central - Vergara Perucich, José Francisco. (Horizon Research Publishing, USA, 2021)
In urban studies, the financialization of housing has become a key aspect in understanding the affordability problems faced by households around the world. The financial interests involved in housing production shift the focus from the provision of a residential habitat to the creation of long-term fixed income capital. However, these studies of high interest to architects have not been studied from the perspective of design and spatial typologies of financialization. This study reviews architectural typology using planimetric information of houses whose main objective is to become profitable products. Based on the critical review of 37 high-rise housing projects in the commune of Estacion Central in Santiago de Chile, a matrix of analysis of the main characteristics of studios and one-bedroom flats is constructed to describe the financed housing unit category in a verticalization model. The research revised official sources for each project, reviewing plans, permits and environmental impact statements that describe the works and their specific analysis. The case study is of high interest because they were installed in a low-income commune of Greater Santiago, capitalized the sector by attracting new residents from higher-income communes, and transformed the urban landscape through residential buildings that are on average 30 stories high. As part of the results, 24 typologies are extracted then summarized in two general types of flats for financial speculation. Also, each case was analyzed by its financial value using the NPV and IRR techniques for economic assessment of investments exposing how profitable these types of projects are. The investment in real estate capital has an impact on the design and formation of typologies arranged for financial speculation with housing. The results of this research illuminate a discussion on the role of architects in the development of housing for financial purposes and propose a discussion on the importance of understanding the architectural aesthetic of financing as a highly relevant disciplinary problem. Collapse.
Keywords: Financing.; Typology.; Verticalization.; Housing; Architecture.